A Novel Method for the Comprehensive Evaluation of Aerospace Components Based on GRAAP. (22nd February 2015) - Xu, Guodong; Guo, Peng; Li, Xuemei; Jia, Yingying
Abstract : The effective evaluation of aerospace components can strongly guarantee the normal running of spacecraft. A novel model called Grey Relational Analysis Based on the Angle Perspective (GRAAP) has been developed in this paper, which can be used to carry out evaluation for the aerospace components by comparing their relation intensities between evaluation component and reference components. Take a regular component as an example; a case study has been introduced based on GRAAP, and the results indicated that the grade of component waiting for evaluation was III, and it can be used in the low orbit spacecraft at least, such as the near earth satellite, and the results were also considered to be more objective than that from some other comprehensive methods. In addition, like other traditional GRA models, GRAAP not only can deal with the evaluation issues, but can also be used to make predictions, make classifications, and so on.